Systematization of requirements definition for software development processes with a business modeling architecture - de Azevedo Jr., Delmir; de Campos, Renato [UNESP] (My University, 2008)
There are several modeling methods, techniques and tools available in order to facilitate the understanding and the analysis of the complexity of the modem organizations. Such methods, techniques and tools are used to make the complex organi7ational practice more understandable. Some of them support information systems development methodologies. Nevertheless, what is observed is lack of integration of the analysis between two domains: the business domain and the system domain. The alignment between the software requirements and the actual need for the business informatization can be improved by means of business modeling techniques. In this work, it was proposed activities for the business modeling to be inserted in the UP (Unified Process) based methodologies or in any other methodology basing on the same principles, with the purpose of systematizing the identification of software requirements aligned with the business objectives. The activities defined in the method comply with the iterative and incremental model, as well as with interfaces well established with the UP pre-established activities, showing some advantages. © 2008 by Springer Science+Business Media New York.
Keywords: Enterprise modeling; Information system; Unified process